Throwing Physics A Curve. - Karlin, S.
It's March, and that means two things for David Peters: the start of the baseball season and appearing on television. Ever since his hometown St. Louis Cardinals won the 2006 World Series, heÃ?Â¿s appeared regularly on local news to explain the mechanics behind curveballs and suchlike.